Perfil epidemiológico e qualidade de vida em crianças e adolescentes submetidos a transplante renal de uma instituição hospitalar de Porto Alegre - RS - Spengler, Lisete Maria (Universidade do Vale do Rio dos Sinos, 2009)
This study points the epidemiological profile and quality of life in children and adolescent renal transplant. It is a cross-sectional study conducted among children and adolescents aged 5 to 18 years old followed at the nephrology clinic of the hospital Santo Antônio, Porto Alegre, Brazil. Data were obtained by two instruments. To characterize the epidemiological profile, we used a questionnaire which addressed socio-demographic information and health conditions. When evaluating the quality of life, it was applied a Child Health Questionnaire-Parent Form 50 (CHQ-PF50). Due to comparing it to a healthy population it was used published data from the validation study's instrument in Brazil. Comparing the results obtained on the scales of the CHQ-PF50 with the data obtained in a population of healthy children (control group) it was perceived that the differences in average scores were lower on all scales except the scale concerning the change in health. It is conclusive for the present purpose, that quality of life related to health in kidney transplant patients from the perception of parents or guardians, was lower than that of healthy children and adolescents of the same age, specifically the terms and physical aspects directly proportional to socioeconomic status and educational level.
Keywords: Transplante renal; Qualidade de vida; Crianças e adolescentes; Renal transplantation; Quality of life; Children and adolescents; ACCNPQ::Ciências da Saúde::Saúde Coletiva